Human decidual macrophages and NK cells differentially express Toll-like receptors and display distinct cytokine profiles upon TLR stimulation - Duriez, Marion; Quillay, Héloïse; Madec, Yoann; El Costa, Hicham; Cannou, Claude; Marlin, Romain; de Truchis, Claire; Rahmati, Mona; Barré-Sinoussi, Françoise; Nugeyre, Marie-Thérèse; Menu, Elisabeth (Frontiers in Microbiology, 2014)
Maternofetal pathogen transmission is partially controlled at the level of the maternal uterine mucosa at the fetal implantation site (the decidua basalis), where maternal and fetal cells are in close contact. Toll-like receptors (TLRs) may play an important role in initiating rapid immune responses against pathogens in the decidua basalis, however the tolerant microenvironment should be preserved in order to allow fetal development. Here we investigated the expression and functionality of TLRs expressed by decidual macrophages (dMs) and NK cells (dNKs), the major decidual immune cell populations. We report for the first time that both human dMs and dNK cells express mRNAs encoding TLRs 1-9, albeit with a higher expression level in dMs. TLR2, TLR3 and TLR4 protein expression checked by flow cytometry was positive for both dMs and dNK cells. In vitro treatment of primary dMs and dNK cells with specific TLR2, TLR3, TLR4, TLR7/8 and TLR9 agonists enhanced their secretion of pro- and anti-inflammatory cytokines, as well as cytokines and chemokines involved in immune cell crosstalk. Only dNK cells released IFN-γ, whereas only dMs released IL-1β, IL-10 and IL-12. TLR9 activation of dMs resulted in a distinct pattern of cytokine expression compared to the other TLRs. The cytokine profiles expressed by dMs and dNK cells upon TLR activation are compatible with maintenance of the fetotolerant immune environment during initiation of immune responses to pathogens at the maternofetal interface.